2015
DOI: 10.31254/jsir.2015.4205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potenial drug-drug interactions among psychitric patients in Ayder referral hospital, Mekelle, Tigray, Ethiopia

Abstract: Introduction: A clinically relevant drug-drug occurs when the effectiveness or toxicity of one medication is altered by the administration of another medicine. Potential Drug-drug interactions are an important cause of adverse drug reactions. Psychiatric patients are increasingly susceptible to drug interactions due to the polypharmacy, nature of the prescribed drugs and most of the drugs prescribed are either enzyme inhibitor or inducers. Objective: To determine the prevalence of the potential drug-drug inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(31 reference statements)
1
5
1
Order By: Relevance
“…Therefore, patients taking a combination of potentially interactive medications need close follow-up. In contrast, the current finding is lower than studies demonstrated in Mekelle, Ethiopia [ 8 ]. The discrepancy in the prevalence of pDDIs among different studies might be related to differences in healthcare approach with pharmacist involvement, differences in alternative medication availability, and differences in the use of software or tools to identify pDDIs in these patients taking interactive medications.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, patients taking a combination of potentially interactive medications need close follow-up. In contrast, the current finding is lower than studies demonstrated in Mekelle, Ethiopia [ 8 ]. The discrepancy in the prevalence of pDDIs among different studies might be related to differences in healthcare approach with pharmacist involvement, differences in alternative medication availability, and differences in the use of software or tools to identify pDDIs in these patients taking interactive medications.…”
Section: Discussioncontrasting
confidence: 99%
“…The single population proportion formula was used to calculate the required sample size by considering the following assumptions: the proportion of drug–drug interactions to be 81.8% ( P = 0.82) [ 8 ], the reliability coefficient for 95% confidence level (Z = 1.96) and 5% margin of error (d = 0.05); n = z 2 pq/d 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 Psychiatric patients are becoming more vulnerable to drug-to-drug interactions (DDI). 9 Since DRPs are a vital issue and a significant number of them are preventable, the specific hazard factors that encourage the event of DRPs are of extensive interest. However, there is no data which has published about the prevalence of and extents of DRPs in the Northwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%